Rancang Bangun Aplikasi Perhitungan Kelayakan Investasi Aset Untuk Mendukung Keputusan Berinvestasi Pada PT Elang Jagad - Oktavianto, Ari; Widodo, Arifin Puji; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Elang Jagad is a metal manufacturing company which produce furnace stoves. During this time the orders company an average of 10,000 units. Company have capacity which can only supply 7,500 units and no unfulfilled residual orders so that orders delayed continuously every month. The company currently can not make an engine  investment decision. This is because the company is not able to analyze the feasibility of the investment calculation. From these problems PT Elang Jagad requires a differential accounting information system for count buy or not to buy the machine, it created an application feasibility calculation of investment assets. This system can count the difference between the value of investments to revenues net cash / net present value, rate of average profit investments / average rate of return, how fast the investment return / payback period, the ratio of investment value with receipts of cash / profitability index and the interest rate of investment / internal rate of return as the basis for measuring the feasibility of the investment.This application is able to generate a report calculating the net present value, payback period, average rate of return, internal rate of return, profitability index and to produce the feasibility of the investment information that can be used to give alternative investment decision-making machinery in PT Elang Jagad.